The invention of Movable-Type Printing in the work of Shen Kuo (1031-1095) - Di Doménico, Luciano Agustín; Mina, Federico Daniel; Santillán, Gustavo E. (Sinología hispánica. China Studies Review, 2022)
This article analyses the jotting n° 307 of the book “Brush Talks from Dream Brook” (Mengxi Bitan), by the scholar Shen Kuo (1031-1095). That jotting presents, by first time in History, the movable-type printing invention. Our analysis of this jotting relates the exposition made by Shen Kuo with the social context of its time, as well as with Shen Kuo’s own personal trajectory as scholar-official of the Northern Song Dynasty (960-1127). The performed examination reveals that Shen Kuo highlights the movable-type printing invention based on its recurrent interest for technical developments; also, it is concluded that the above-mentioned interest must not be isolated from Shen Kuo´s trajectory within the Court, and, finally, that book printing was a noteworthy phenomenon in the society of Shen’s times, for both socioeconomic and political reasons.